Active Immunotherapy Used Alone for Maintenance of Patients with Acute Myeloid Leukaemia. Issue 5892 (8th December 1973) - Freeman, Charles B.; Harris, Rodney; Geary, Colin G.; Leyland, Michael J.; MaCiver, John E.; Delamore, Irvine W.
Abstract : A total of 32 patients suffering from acute myeloid leukaemia were initially treated with daunorubicin and cytosine arabinoside, and eight who achieved full remission were given a brief cytoreduction course of cyclophosphamide and thioguanine. Of these eight patients seven were then actively immunized with 10 irradiated allogeneic acute myeloid leukaemia cells and B.C.G. at weekly intervals. Six of these patients have survived in apparent good health for more than one year. Bone marrow changes suggestive of relapse were used as an indication for further short courses of chemotherapy, and except on single occasions in two different patients clinical relapse has been prevented. The average duration of first (bone marrow) remission appears to be comparable with the best achieved in trials using regular chemotherapy for maintenance, though criteria for determining relapse may be different. The rate of reinduction of remissions (bone marrow) in this series was high, with a subsequent increase in overall survival time. Possible explanations for the high rate of reinduction include, firstly, the effects of active immunization with specific leukaemia antigen; secondly, non-specific adjuvant effect; thirdly, avoidance of drug resistance; and, fourthly, early diagnosis of relapse by frequent bone marrow examinations.